THE PROTAGONIST’S IMPROPER BEHAVIOR IN TETSUKO KUROYANAGI’S TOTTO-CHAN: THE GIRL AT THE WINDOW - Mahbubah, Umi Syahara; Sahri, Zulfan (Universitas Islam Sumatera Utara, 2025)
This research aims at uncovering the kinds of improper behavior performed by the protagonist character in the novel “The Girls at the Window” written by Tetsuko Kuroyanagi. This study explores the types and causes of improper behaviors exhibited by the protagonist in Tetsuko Kuroyanagi’s novel, Totto-Chan: The Girl at the Window. Using a qualitative descriptive method, the study identifies behaviors such as classroom disruption, damage to school property, and dishonesty toward parents. He is making a mess in the classroom, damaging school facilities and lying to parents. This research uses qualitative descriptive method. Under qualitative descriptive, this research completes its analysis process and findings by describing and illustrating the data that has been collected. It is by explaining the improper behavior and examples of bad behavior of the protagonist from the data collected from the novel in the forms of quotation. The results of this research are to find out what bad behavior the protagonist does, and the reasons why the protagonist does it.